TEKNOLOGI AUGMENTED REALITY SEBAGAI MEDIA BELAJAR BERBASIS ANDROID BAGI SISWA KELAS 4 SD NEGERI 11 SESETAN - Made Bhismayoga; I Gede Putu Megayasa; Ni Luh Gede Ambaradewi (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2024)
Low learning interest among students, especially fourth-grade elementary school students, often becomes an obstacle in achieving optimal learning outcomes. To help make the learning process more effective and efficient, educational media are used as intermediaries between educators and learners that connect, provide information, and deliver messages. With the advancement of technology, the education world faces new challenges in applying technology to learning activities, particularly in the development of educational media. One technology that can support learning is Augmented Reality (AR). The main component of Augmented Reality is a 3D object that appears when a marker is scanned by software or an application. This will make students more interested in learning because of the animated 3D objects. In this research, the researcher developed